Characterization of Genetic Variants in the SLC5A5 Gene and Associations With Breast Milk Iodine Concentration in Lactating Women of African Descent: The NUPED Study - Siro, Sicelosethu S.; Baumgartner, Jeannine; Schoonen, Maryke; Ngounda, Jennifer; Malan, Linda; Symington, Elizabeth A.; Smuts, Cornelius M.; Zandberg, Lizelle (Frontiers in Nutrition, 2021)
Background. The sodium iodide symporter is responsible for the transfer of iodine into breast milk and is encoded for by the SLC5A5 gene. The role of genetic variants in the SLC5A5 gene locus in relation to the transfer of iodine from plasma into breast milk in healthy lactating individuals has, to our knowledge, not been explored. Objective. To identify and characterize possible genetic variants of the SLC5A5 gene in women of African descent living in urban South Africa, and to study associations with breast milk iodine concentrations (BMIC) in lactating women. Methods. This study is affiliated to the Nutrition during Pregnancy and Early Development (NuPED) cohort study (n=250 enrolled pregnant women). In a randomly selected sub-sample of 32 women, the SLC5A5 gene was sequenced to identify known and novel variants. Of the identified variants, genotyping of selected variants was performed in all pregnant women who gave consent for genetic analyses (n=246), to determine the frequency of the variants in the study sample. Urinary iodine concentration (UIC) in spot urine samples and BMIC were measured to determine iodine status. Associations of SLC5A5 genetic variants with BMIC were studied in lactating women (n=55). Results. We identified 27 variants from sequencing of gene exomes and ten variants were selected for further study. There was a significant difference in BMIC between the genotypes of the rs775249401 variant (P=0.042), with the homozygous GG group having lower BMIC (86.8 (54.9 ‒ 167.9) µg/L) compared to the (A) allele carriers rs775249401(AG+AA) (143.9 (122.4 ‒ 169.3) µg/L) (P=0.042). Of the rs775249401(GG), 49% had UIC <100 µg/L and 61% had BMIC <100 µg/L. On the other hand, 60% of the rs775249401(AG+AA) carriers had UIC <100 µg/L, and none had a BMIC <100 µg/L. Conclusion. Our results suggest that A-allele carriers of rs775249401(AG+AA) are likely to have higher iodine transfer into breast milk compared to the homozygous GG counterparts. Thus, genetic variations in the SLC5A5 gene may play an important role in the transfer of iodine from plasma into breast milk and may partially explain inter-individual variability in BMIC.